Optimization of a large‐volume injection method for compound‐specific isotope analysis of polycyclic aromatic compounds at trace concentrations. (6th November 2015) - Blessing, Michaela; Jochmann, Maik A.; Haderlein, Stefan B.; Schmidt, Torsten C.
Abstract : Rationale: Compound‐specific isotope analysis (CSIA) of persistent organic contaminants can be used for source apportioning in the environment if appropriate sensitivity can be achieved. This paper describes the optimization and validation of a sensitive analytical approach for the determination of the carbon isotope composition of semi‐volatile organic compounds, such as polycyclic aromatic hydrocarbons (PAHs). Methods: Analyses are based on the introduction of up to 150 μL of organic extracts by means of programmed temperature vaporization–large‐volume injection combined with gas chromatography coupled to isotope ratio mass spectrometry (PTV‐LVI‐GC/IRMS). To allow for the analysis of more volatile, low‐molecular‐weight PAHs, the PTV injector was equipped with a sub‐ambient/cryogenic cooling. Accuracy, precision, linearity and determination limits for application in isotope analysis were evaluated for a set of individual PAHs ranging from two‐ to five‐ring molecular structures. The method was exemplified by determining the δ 13 C values of individual PAHs in soil samples in a source apportionment study at a contaminated site. Results: The choice of PTV injection parameters is crucial to prevent isotope fractionation during injection and largely depends on the analytes to be determined. The observed isotope fractionation effect on semi‐volatiles depends on the applied solvent and injection temperature and demonstrates the importance of performing appropriate tests with given PTV parameters for each of the compounds of interest. The proposed PTV‐LVI‐GC/IRMS method allows the carbon isotope ratio (δ 13 C value) of individual PAHs to be determined accurately and precisely at concentrations of 0.04–0.1 ng μL −1 even for volatile PAHs such as naphthalene or acenaphthene. Conclusions: LVI with PTV injector cooling allows for the isotopic analysis of volatile and semi‐volatile PAHs at trace concentrations, thus considerably expanding the applicability of CSIA in environmental studies. Copyright © 2015 John Wiley & Sons, Ltd.